Paleo-environment and provenance in a lacustrine shallow-water delta-meandering river sedimentary system: insights from the Middle–Upper Jurassic formations of the Fukang Sag of Junggar Basin, NW China. Issue 5 (4th July 2019) - Luo, L.; Gao, X.; Tan, X.; Gluyas, J.; Wang, J.; Kong, X.; Huang, J.; Shao, H.; Qu, F.
Abstract: The Middle–Upper Jurassic Shishugou Group in the central Junggar Basin was deposited in a lacustrine shallow-water delta-meandering river sedimentary system. The integrated petrological (thin-section, granularity and heavy minerals analysis), geochemical (trace elements and rare earth elements analysis) and geophysical analyses (well logging and 3D-seismic slice analysis) are used to determine redox conditions, paleoclimate, paleosalinity, provenance and sedimentary evolution extant during deposition of the Shishugou Group: (1) the redox condition changed from a weak anoxic/oxic condition to a strongly oxic condition; (2) the climate changed from humid to hot and arid in the Middle–Late Jurassic, which may have resulted in the lake water having slight–medium salinity; (3) the relatively distant northeastern provenance from the Kelameili Mountain is the most important sediment source; and (4) the south provenance from the Tianshan Mountains (Bogeda Shan) decreases with the development of the sag piedmont, which supplies sediments to the southeastern Fukang Sag. The sedimentary environment changed from a lacustrine shallow-water delta to a meandering river during the deposition of the Shishugou Group. The shallow-water meandering river delta was characterised by pervasive mudstones with oxide colours, thin single-layer sand bodies (1–15 m, mean 3 m), relatively low sand–strata ratios (0.2–0.5) and the absence of progradation, mouth bars and reverse rhythms. The gentle slope is the primary condition necessary for the formation of a shallow-water meandering river delta. Paleo-environment (climate change from warm-humid to hot-arid) and the stable and remote Kelameili Mountain provenance played critical roles in the development and evolution of lacustrine–delta-meandering river sedimentary systems.